DESIGN OF A WORDPRESS BASED E-COMMERCE WEBSITE AND INTEGRATION OF CRYPTOCURRENCY PAYMENT GATEWAY - Anggoro, Restu; Susanto, Erliyan Redy (Jurnal Teknik Informatika (Jutif), 2024)
The Internet has become one of the main media, especially e-commerce transactions, which are increasingly popular and play an important role in the growth of online businesses. The RestLyfe store uses the Itemku platform, which uses a Business to Customer (B2C) and Customer to Customer (C2C) model, to sell digital products such as digital vouchers and game keys. However, some of the issues faced when using the platform include high costs, limited market reach, and payment methods that can only be used by certain customers. Building an e-commerce website and adding a cryptocurrency payment gateway will hopefully solve these problems. To achieve this goal, an e-commerce website based on the WordPress content management system (CMS) with the WooCommerce plugin will be built. This plugin will incorporate a cryptocurrency payment gateway and facilitate transaction design. To collect related data, observation and literature review were conducted. The waterfall model System Life Cycle Development (SDLC) method will be used to build the e-commerce website. The results and conclusions of this study show that the website built can solve the problem with implementation results that meet the needs of the initial analysis, and the results of black box testing conducted on the website show good results. In addition, this study demonstrates the use of modern sales strategies for cryptocurrencies and the optimization of the latest technologies. Thus, the e-commerce site offers more opportunities to reach the target market and meet the needs of an increasingly digitized market.